Del criterio cuantitativo al criterio cualitativo en la evaluación de impacto ambiental - Kahatt, Karim (2013)
The essay discusses the criteria available in Peru’s environmental impact assessment regime for mandatory modification of environmental impact studies as a result of the modification of the underlying project. The paper identifies the gaps in the cross-sector legislation on environmental impact assessment, and the deficiencies of sector-specific legislation on environmental impact assessment, which have privileged quantitative criteria associated to the size of the project, over qualitative criteria associated to the real impact of the amendment of the project.